Abracadabra 5.0 / Muhammad Usamah Mohd Ridzuan, Aileen Farida Mohd Adam and Nur Afiqah Ab. Latif - Mohd Ridzuan, Muhammad Usamah; Mohd Adam, Aileen Farida; Ab. Latif, Nur Afiqah (Academy of Language Studies, 2023)
The Academy of Language Studies and Pre-Diploma Unit at UiTM Pulau Pinang Branch organized the 5th semester pre-diploma poster competition, Abracadabra 5.0, which took place from January 16th to 28th, 2023. This program was open to pre-diploma students students who were taking ELC010 and ELC030 (English for Pre- Diploma) and served as a platform for them to apply and practice their English in a real and competitive context. The competition aimed to improve the students' communication skills and confidence level in English. The theme for the competition was 'Creating a Sustainable Future'. During the selection phase from January 16th to 27th, 32 groups consisting of a total of 128 contestants were chosen by their respective lecturers. These groups, representing their classes, then competed in the main event of the competition on January 28th, 2023 in front of a judging panel composed of 16 judges. All contestants demonstrated impressive skills and talents in decorating their booths and presenting in front of the crowds.